IMPLEMENTATION OF INTERACTIVE MULTIMEDIA SEMAPHORE AND MORSE CODE IN SCOUTS OF VOCATIONAL SCHOOL 1 PRAYA CENTRAL - Pratama, Muhamad Ikhsan; Putra, I Putu Satra Udyana; Adnyana, I Nyoman Widhi; Yasa, I Wayan Adi Putra; Setiawan, I Nyoman Anom Fajaraditya; Jayanegara, I Nyoman (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Semaphore and Morse code are skills that a scout must have. However, these skills face various problems such as having a conventional pocketbook or limited extracurricular time which causes a lack of student understanding. As a result of this problem, the solution offered is interactive multimedia which can be accessed via smartphone. Multimedia is designed in a portrait model and has several simple, easy-to-access, easy-to-understand features to help become a learning medium with the aim of being able to be used according to its function and benefits. The goal to be achieved in this research is to build interactive multimedia material on semaphore and Morse code scouts at SMKN 1 Praya Tengah. The author uses the Multimedia Development Life Cycle method, with several process stages, concept creation, design planning, material collection, manufacturing process, testing, and distribution. After testing using a questionnaire targeting media experts, material experts, and students, the questionnaire validation results obtained were 90% for media experts, 76.6% for material experts, and 88.6% for students. Based on the data, it can be concluded that this interactive learning media is suitable for use as a training medium. The results of this research are an Android-based semaphore and Morse code scout application in apk format.